Rancang Bangun Sistem Pemadam Api pada Malam Hari Berbasis Arduino Uno - Chaterine Tamara Ginting; Sartika Yuliana Br Silaen (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Fires can occur anywhere and at any time both at home, at school and in other places other than that can occur during the day and night. Fires occur as a result of a fire that is not detected as quickly as possible and the existing fire is getting bigger which results in a fire. But the possibility of a fire at night will be greater due to the homeowner in a state of sleep. The above will make every homeowner feel uneasy and worried. In the design of this system fire detection is based on the direction of the wind and fire extinguishing automatically by the water pump at night it happens due to an integrated system of fire sensors, compass sensors with water pumps. In this case the function of the water pump system is controlled by information from the fire sensor. The water pumping system will work if it is informed by sensors that a fire has been detected. In addition this system is equipped with a compass sensor to determine the hotspot based on the direction of the wind. The location of the hotspot will be informed to the user via GSM SIM 800L. In addition to information that a fire fighting fire has been detected, it will also be notified to users. The expected outcome of this design is to help homeowners to prevent house fires because this system automatically detects fires and extinguishes fires at night and informs users of the detected and extinguished fires automatically. So that the users of this system can sleep well at night without feeling worried.